Upaya Mengatasi Kesulitan Belajar Siswa pada Materi Gambar Bentuk Tiga Dimensi Melalui Penerapan Model Project Based Learning Dengan Menggunakan Media Power Point - Lisna Pasaribu (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
This classroom action research was motivated by students who were still having difficulty learning the Three-Dimensional Drawing material in class IV at SD Negeri 7 Kuala Kencana. This is due to the lack of variety in the learning process in class, causing their interest and motivation to be low in participating in the learning process in class. This Classroom Action Research aims to overcome the difficulties experienced by students by implementing the Project Based Learning (PjBL) learning model using power point media in the student learning process in class. The data in this research was obtained through observation, tests and documentation. Based on research data from pre-action to cycle II, data was obtained that student learning outcomes in the learning process through implementing the PjBL model using power point media had increased significantly from previous learning using the lecture method. So, the conclusion is that the application of the PjBl model using power point media can overcome students' learning difficulties so that it has an impact on increasing student learning outcomes, especially in Three-Dimensional Shape Drawing material at SD Negeri 7 Kuala Kencana.